Ecotoxicology of Potamotrygoninae freshwater stingrays: bioaccumulation, toxicological risks, and conservation implications - Barbosa, Neuciane Dias; Wosnick, Natascha; Chaves, Ana Paula; Giareta, Eloísa Pinheiro; Leite, Renata Daldin; Charvet, Patricia; Hauser-Davis, Rachel Ann (Frontiers in Marine Science, 2025)
Obligate freshwater stingrays of the Potamotrygoninae subfamily are endemic to South America and confined to freshwater systems heavily impacted by anthropogenic activities. These pressures often lead to habitat degradation, with unknown impacts on these species’ physiology, behavior, ecology, and survival. Given the increasing pollution of aquatic environments and potential lethal and sublethal effects on exposed biota, this study aimed to review the state of knowledge on the ecotoxicology of species within the Potamotrygoninae subfamily, which includes four genera, namely Heliotrygon, Paratrygon, Plesiotrygon, and Potamotrygon. A systematic review of peer-reviewed articles published in English retrieved seven studies, all focused on Potamotrygon genus stingrays. To date, no investigations have been conducted on species from the other three genera. Five of the reviewed studies focused on the evaluation of metals and metalloids, predominantly assessing mercury in muscle tissue. Additionally, two manually included studies addressed other contaminants, one examined plastic contamination in the intestinal tract of Potamotrygon leopoldi, and the other analyzed morphological deformities in Potamotrygon marquesi, potentially linked to chemical contamination. Some studies focused on human health risk assessments, as freshwater stingrays are routinely consumed by humans in several of their distribution areas. No biomarker assessments have been conducted to date, further restricting evaluations of the species’ health and resilience to environmental stressors. The recovered studies were conducted in four South American countries, with most carried out in Brazil. Knowledge gaps and future research directions are discussed, alongside details of the studies conducted to date.